A Systematic Review On Novel Twincretin; Tirzepatide in Treatment of Type-II Diabetes Mellitus. - Dr. Avula Naveen; Dr. Mr Sravani; Dr .Syed Ilias Basha (International Journal of Pharma and Bio Sciences, 2022)
Type 2 Diabetes Mellitus(T2DM) is a chronic progressive disease characterized by hyperglycemia and progressive dysregulation leading to microvascular and macrovascular complications. Glucagon-like peptide 1 (GLP-1) based therapy is an established treatment option for the management of type 2 diabetes mellitus (T2DM) and is recommended early in the treatment algorithm owing to glycaemic efficacy, weight reduction, and favourable cardiovascular outcomes. A glucose-dependent insulinotropic polypeptide (GIP), on the other hand, was thought to have no potential as a glucose-lowering therapy because of observations showing no insulinotropic effect from supraphysiological infusion in people with T2DM. However, emerging evidence has illustrated that, co-administration of GLP-1 and GIP has a synergistic effect, resulting in significantly increased insulin response and glucagonostatic response, compared with separate administration of each hormone. These observations have led to developing a dual GIP/GLP-1 receptor agonist, known as a ‘twincretin’ called Tirzepatide. In this paper, we have reviewed different clinical trials to evaluate the efficacy and safety of Tirzepatide over conventional antidiabetic drugs like Metformin and newer GLP1-receptor agonists in the treatment of T2DM. We consider the reduction of glycated hemoglobin (HbA1C) and body weight as our objectives in our study. In May 2022, FDA approved Tirzepatide for the treatment of T2 DM, which is a novel dual GIP/GLP-1 receptor agonist formulated as a synthetic peptide containing 39 amino acids, based on the native GIP sequence. The newly approved drug has shown excellent results in lowering blood glucose and weight loss. Pre-clinical trials and Phase 1, Phase 2, and Phase 3 clinical trials compared Tirzepatide vs Placebo or GLP-1 receptor agonists which concluded that Tirzepatide potent glucose-lowering and weight loss causing agent with adverse effects comparable to those of established GLP-1 receptor agonists. It is too early to comment on the long-term efficacy, safety, and cardiovascular outcomes of tirzepatide.